A simple cryotransfer method for 3D electron diffraction measurements of highly sensitive samples - Gurung, Kshitij; Uran, Erik; Motaln, Klemen; Brázda, Petr; Radan, Kristian; Lozinšek, Matic; Palatinus, Lukáš (Journal of applied crystallography, 2025)
The accurate characterization of highly sensitive materials using 3D electron diffraction (3D ED) is often challenged by sample degradation caused by exposure to moisture, air, temperature variations and high vacuum during the transfer and introduction into the transmission electron microscope (TEM). A cryogenic sample-transfer protocol is presented here, designed to enable the safe and effective transfer of reactive samples into the TEM, ensuring an inert and moisture-free environment throughout the process. The protocol was validated by redetermining the crystal structures of the moisture-sensitive, strongly oxidizing and highly reactive compounds XeF2, XeF4 and XeF2·XeF4 cocrystal. Crystal structures of all three compounds were successfully solved ab initio and dynamically refined, yielding results that showed good agreement with the previously reported X-ray and neutron diffraction structures. This approach holds significant promise for advancing the study of other reactive and moisture-sensitive samples, enabling precise structural characterization in cases where traditional TEM sample preparation is unsuitable.
Keywords: cryotransfer; xenon fluorides; noble-gas compounds; 3D electron diffraction